Aliphatic nitro compounds from roots of Astragalus sikokianus (Fabaceae) in Korea. (June 2015) - Na, Chae Sun; Lee, Yong Ho; Kim, Tae Wan; Murai, Yosinori; Hong, Sun Hee
Highlights: Four nitro compounds were isolated from Astragalus sikokianus for the first time. Three nitro compounds were identified as 3-nitropropanoic acid glucosides. A. sikokianus is chemotaxonomically related to Sect. Uliginosi of genus Astragalus .